(untitled) (British Journal of Global Ecology and Sustainable Development, 2024)
This study provides an analysis of the present mechanical and agrochemical properties of irrigated meadow soils in the Besharyk district of the Fergana region. It also discusses the ongoing research work conducted within the country on this subject. Furthermore, it delves into how soil characteristics change when a single type of crop is cultivated over an extended period.